A method and application of preparing graphene composite copper strip using copper waste

Through powder metallurgy and medium-temperature continuous extrusion processes, graphene is fully extruded into the lattice void of copper waste, solving the high energy consumption and serious pollution problems of the existing copper plate and belt production process, realizing the preparation of high-performance graphene composite copper plate and belt, and improving the multiple properties of the materials.

CN119140824BActive Publication Date: 2025-03-07BEIJING JINPENG ZHENXING COPPER IND CO LTD

Patent Information

Application Number
CN202411661383.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-07
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing copper plate belt production process has problems such as high energy consumption, severe smoke pollution, long process cycle, complex process, large loss and serious segregation problems of adding trace elements, and it is difficult to meet the material needs of high corrosion resistance, high conductivity, high elasticity and high strength.

Method used

Powder metallurgy combined with medium-temperature continuous extrusion process, graphene is added to copper waste, and high-performance graphene composite copper plate tape is formed through semi-melt stirring and continuous extrusion process.

Benefits of technology

It realizes efficient pollution-free recycling of copper waste, improves the strength, conductivity, corrosion resistance, high temperature resistance, wear resistance and other properties of composite materials, and reduces production energy consumption and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140824B_ABST
    Figure CN119140824B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of powder metallurgy, and more particularly to a method for preparing a graphene composite copper strip by powder metallurgy combined with a medium-temperature continuous extrusion process using copper waste. According to the application scenario of the graphene composite copper strip, copper waste containing different components is selected; the copper waste is crushed into copper block fragments; 0.1-8% of graphene by mass is added to the copper block fragments, and a first-size mixed powder is formed by grinding; the first-size mixed powder is semi-melted and stirred to form a graphene-copper mixed substrate, which is continuously extruded; the graphene composite copper strip blank is processed with reference to a conventional copper cold rolling process to obtain a graphene composite copper strip. The present invention combines a medium-temperature continuous extrusion process with a powder metallurgy process to realize the recycling of copper waste in a non-smelting manner and the production of a matrix of a high-performance graphene composite copper strip. The present invention also discloses the application of the graphene composite copper strip.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of powder metallurgy, and in particular to a method and application of preparing a graphene composite copper strip by utilizing copper waste through powder metallurgy combined with a medium-temperature continuous extrusion process. Background Art

[0002] In the current production of non-ferrous copper plates and strips, a large number of new electrolytic copper and electrolytic zinc are used in furnace production. This production method makes it impossible to reduce energy consumption and emissions. According to statistics, compared with primary copper, the use of each ton of recycled copper (recycled scrap copper) can reduce coal consumption by 1,054 tons, save 395 tons of water, reduce solid waste by 380 tons, and reduce sulfur dioxide emissions by 0.137 tons. Through the above statistical data, we can intuitively realize that the use of recycled copper is of great significance to environmental protection, carbon emission reduction, and solid waste pollutant emission reduction.

[0003] There are two main ways to reuse copper waste today: direct and indirect. Whether it is direct (smelting high-quality scrap copper directly into finished products) or indirect (smelting scrap copper into anode copper, and then electrolytically smelting it into electrolytic copper), smelting is indispensable. How to use recycled scrap copper to produce high-precision copper alloys without smelting is a difficult problem for non-ferrous copper plates and strips.

[0004] In addition, the mainstream production process of copper strips is through horizontal continuous casting, vertical casting and upward casting rod re-extrusion process. The process cycle is long and the high temperature volatilization of raw materials in the smelting and casting process causes serious smoke pollution. Due to the long production process, the energy consumption of the production process will increase. The existing grades are single copper or added with trace elements such as Sn, Fe, P, Mg, Al, Ni, Si, rare earth, etc. for strengthening. The addition process is complicated, the loss of added elements is large, the difficulty is high, and various segregation problems are serious.

[0005] Due to the increasingly stringent requirements for the environment, use, fatigue resistance and corrosion resistance of electrical control, the single copper alloy material produced based on the existing preparation process can no longer meet the needs of enterprises and the market for highly corrosion-resistant, highly conductive, highly elastic and highly strong copper sheet and strip materials. Summary of the invention

[0006] In order to solve at least one of the above technical problems, the present invention proposes a method and application of preparing graphene composite copper plates and strips by using copper waste through powder metallurgy combined with medium-temperature continuous extrusion process, so as to solve the problem of non-smelting recycling and reuse of copper waste and production of high-performance graphene composite copper plates and strips.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] The first aspect of the present invention provides a method for preparing a graphene composite copper strip using copper waste, comprising the following steps:

[0009] S1, selecting copper waste containing different components according to the application scenario of graphene composite copper strip;

[0010] S2, crushing the copper waste into copper block fragments;

[0011] S3, according to the application scenario of the graphene composite copper strip, adding 0.1-8% by mass of graphene to the copper block scrap, and grinding to form a first size mixed powder;

[0012] S4, semi-melting and stirring the first size mixed powder, so that the graphene is evenly filled in the copper fine crystal structure to form a graphene-copper mixed substrate;

[0013] S5, continuously extruding the graphene-red copper mixed substrate so that the graphene as a filling element is completely extruded into the lattice gap of the red copper fine crystal structure to form a graphene composite copper strip blank;

[0014] S6, processing the graphene composite copper strip blank according to a conventional copper cold rolling process to obtain a graphene composite copper strip.

[0015] Preferably, the size of the copper block fragments is 1-2 cm, and the particle size of the first-size mixed powder is less than 50 μm.

[0016] Preferably, S4 comprises the following steps:

[0017] S41, feeding the first size mixed powder into a circular feeder, and injecting an inert gas into the circular feeder;

[0018] S42, heating the circular feeder to 450-500° C. to make the first size mixed powder reach a semi-molten state to form the graphene-copper mixed substrate;

[0019] S43, rotating and shearing the graphene-copper mixed substrate through a twin screw, stirring for 10-20 minutes, and then conveying it to the discharge port of the circular feeder.

[0020] Preferably, the circular feeder is made of super austenitic stainless steel 1.4652, and the twin-screw pushing pressure range is 35-45 MPa. At this time, the density of the graphene-copper mixed substrate is more than 65% of the normal solid theoretical density.

[0021] Preferably, S5 comprises the following steps:

[0022] S51, sending the graphene-copper mixed substrate into a continuous extruder;

[0023] S52, setting the extrusion cavity temperature of the continuous extruder to 800-950° C., setting the extrusion pressure to not less than 1000 MPa, and continuously extruding the graphene-red copper mixed substrate to obtain the graphene composite copper strip blank.

[0024] Preferably, the continuous extruder is a Conform continuous extruder.

[0025] Preferably, the graphene composite copper strip has a thickness of 16-25 mm and a width of 10-600 mm.

[0026] Preferably, the graphene forms a linear elongated structure for efficient electron transmission along the rolling and extrusion directions in the graphene composite copper strip.

[0027] Preferably, the copper scrap contains the following raw material components in percentage by mass: Cu: 95-99.5%, Ag: 0.001-0.1%, P: 0.001-0.4%, Au: 0.0001-0.1%, graphene: 0.1-6%, and the balance is one or more of Ni, Cr, Zn, Fe, Nb, Sn, Ti, Bi, Al, Pt, and B, and the total amount is less than 0.5%;

[0028] Or, the copper scrap contains the following raw material components in percentage by mass: Cu: 96-99.5%, Ni: 0.01-0.4, Sn: 0.01-0.1%, Ag: 0.001-0.1%, P: 0.01-0.1%, Au: 0.0001-0.1%, graphene: 0.1-4%, and the balance is one or more of Cr, Zn, Fe, Nb, Ti, Bi, Al, Pt, and B, and the total amount is less than 0.5%;

[0029] Or, in terms of mass percentage, the copper scrap contains the following raw material components: Cu: 97-99.5%, Fe: 0.01-0.5%, Ni: 0.01-0.5%, Ag: 0.001-0.01%, P: 0.01-0.1%, Au: 0.0001-0.1%, graphene: 0.01-5%, and one or more of other trace elements Cr, Zn, Nb, Ti, Bi, Al, Pt, and B, and the total amount is less than 0.5%;

[0030] Or, the copper scrap contains the following raw material components in percentage by mass: Cu: 98-99.5%, Ag: 0.001-0.5%, Au: 0.0001-0.1%, graphene: 0.1-8%, and the balance is one or more of Ni, Cr, Zn, Fe, Nb, Sn, Ti, Bi, Al, Pt, B, and P, and the total amount is less than 0.5%;

[0031] Or, measured by mass percentage, the copper scrap contains the following raw material components: Cu: 99.2-99.8%, Fe: 0.01-0.5%, Au: 0.0001-0.1%, graphene: 0.1-6%, and the balance is one or more of Ag, Ni, Cr, Zn, Fe, Nb, Sn, Ti, Bi, Al, Pt, B, and P, and the total amount is less than 0.5%.

[0032] The second aspect of the present invention provides a method of preparing a graphene composite copper strip using copper waste as described in the first aspect and applying it to conductive elastic components in aerospace, marine, automobile and electrical appliances.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. The present invention uses a powder metallurgy process combined with a medium-temperature continuous extrusion process to fully extrude graphene as a filling element into the lattice gap of copper waste, thereby forming a high-performance graphene composite copper strip with high strength, high thermal conductivity and high electrical conductivity. This preparation method not only realizes the efficient and pollution-free direct recycling of copper waste, but also realizes a substantial improvement in the physical and chemical properties of the composite material prepared from copper waste in terms of strength, conductivity, corrosion resistance, high temperature resistance, wear resistance, etc.

[0035] 2. The present invention uses a semi-melting crushing shear stirring process to effectively crush the columnar and dendritic crystals in the organizational structure of the graphene-red copper mixed substrate, limiting the continued growth of the recrystallized organization. In addition, in the semi-melting crystal state, the crushing and stirring mechanical vibration can not only increase the number of hard crystal nuclei, but also more evenly distribute graphene in the hard crystal nucleus organization of the refined red copper waste, effectively improving the physical and chemical properties of the organizational structure. At the same time, it also prepares the composite material for the subsequent extrusion preparation of graphene composite copper strips.

[0036] 3. The present invention adopts a continuous extrusion process, and the extrusion pressure of the continuous extruder is set to not less than 1000Mpa. Thus, an extrusion force of not less than 1000MPa can be continuously generated. At this time, the solid-liquid ratio of the substrate is less than 40%, and the arrangement between the elements in the matrix is ​​disordered. Through extrusion and the subsequent cold rolling process, graphene forms a linear extension structure along the rolling and extrusion direction in the organization. These linear extension organizations constitute an efficient transmission channel for electrons, effectively improving the electrical conductivity of the composite material. Based on the high conductivity of graphene itself, the added graphene reduces the potential difference of the elements in the organization, greatly reduces the later galvanic cell reaction of the material, and enhances the corrosion resistance of the material matrix.

[0037] 4. The raw materials of the present invention are copper waste containing different components, which can well solve the problem of continuous remelting production of copper waste recycled by the society. At the same time, it reduces the production cycle of copper plates and strips, and achieves the purpose of producing high-performance copper plates and strips without the discharge of waste water, waste slag and waste gas, low energy consumption, and efficient use of waste copper scraps. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The present invention is a flow chart of a method for preparing graphene composite copper strips by using copper waste. DETAILED DESCRIPTION

[0039] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. It is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments of the present invention.

[0040] Embodiment 1

[0041] Please refer to Figure 1 As shown, a method for preparing graphene composite copper strip from copper waste comprises the following steps:

[0042] S1, according to the application scenario of graphene composite copper strip, select copper waste containing different components.

[0043] It should be noted that the purpose of selecting copper scraps containing different components is to prepare graphene composite copper strips with different physical and chemical properties by screening copper scraps with different components through the following preparation process. Specifically, the physical properties include but are not limited to high electrical conductivity, high thermal conductivity, high strength, high toughness and high specific surface area. The chemical properties include but are not limited to corrosion resistance, oxidation resistance and heat resistance.

[0044] Compared with the existing production process of copper plates and strips, various trace elements need to be added, and the addition process is complicated, the loss of added elements is large, the difficulty is high, and various segregation problems are serious. This implementation uses copper waste containing different components to solve the problem of continuous recycling of copper waste in society. At the same time, it reduces the production cycle of copper plates and strips, and achieves the purpose of producing high-performance copper plates and strips without the discharge of waste water, waste slag, and waste gas, low energy consumption, and efficient use of waste copper scraps.

[0045] S2, crushing the copper waste into copper block fragments.

[0046] It should be noted that the copper waste in this embodiment is crushed by a metal crusher. In order to facilitate the subsequent grinding or ball milling of the copper block fragments into powder of a specified particle size, the size of the copper block fragments in this embodiment is controlled to be 1-2 cm.

[0047] S3, according to the application scenario of the graphene composite copper strip, add 0.1-8% by mass of graphene to the copper block scraps, and grind to form a first-size mixed powder.

[0048] It is understood that by ball-milling the copper block fragments using a grinder, the graphene and the copper block fragments can be evenly mixed, which helps to improve the physical and chemical properties of the composite material formed by the two to play a synergistic role. In this embodiment, the particle size of the first size mixed powder is less than 50 μm.

[0049] S4, semi-melting and stirring the first size mixed powder so that the graphene is evenly filled in the copper fine crystal structure to form a graphene-copper mixed substrate.

[0050] In this embodiment, a circular feeder is used to semi-melt, stir and feed the first size mixed powder, wherein the feeding pipe of the circular feeder is a circular feeding pipe equipped with a relatively rotating twin screw.

[0051] Considering the need to semi-melt the first-size mixed powder, a heating device is provided on the circular feeding tube in this embodiment. The temperature in the circular feeding tube is raised to 450-500°C by the heating device, so that the first-size mixed powder is in a semi-molten state. At the same time, the graphene-copper mixed substrate is rotated and broken by the relatively rotating twin screws to obtain a fine-grained structure of copper. The stirring time in this embodiment is 10-20 minutes.

[0052] It is understandable that the columnar and dendritic crystals in the organizational structure of the graphene-copper mixed substrate are effectively broken through the semi-melting crushing shear stirring process, which limits the continued growth of the recrystallized organization. In addition, in the semi-melting crystal state, the crushing and stirring mechanical vibration can not only increase the number of hard crystal nuclei, but also more evenly distribute the graphene in the hard crystal nucleus organization of the refined copper waste, effectively improving the physical and chemical properties of the organizational structure. At the same time, it also prepares the composite material for the subsequent extrusion preparation of graphene composite copper strips.

[0053] Considering that the semi-molten graphene-copper mixed substrate may undergo an oxidation reaction with oxygen in the air, inert gas, specifically argon, is injected into the circular feeder in this embodiment.

[0054] In addition, injecting argon into the circular feeder can effectively control the oxygen content in the circular feeder, thereby ensuring that the oxygen content in the tissue structure is effectively controlled.

[0055] In order to ensure that the density of the semi-molten structure can reach more than 65% of the normal solid theoretical density, the pushing pressure range of the twin screw in this embodiment is 35-45MPa. Under this pressure, the density of the semi-molten structure (graphene-copper mixed substrate) will reach more than 65% of the normal solid theoretical density, thereby ensuring the initial formation of the structure and the stability of the formed crystalline structure.

[0056] It should be noted that since the inside of the round feeder needs to be heated to 450-500°C, the material of the round feeder must have sufficient high temperature strength and hardness, high tempering temperature resistance, good heat resistance, good machining properties, good material toughness, low thermal expansion coefficient and good thermal conductivity.

[0057] Based on the above factors, the circular feeder in this embodiment adopts super austenitic stainless steel 1.4652.

[0058] Specifically, super austenitic stainless steel 1.4652 is called 654SMo or S32654. The melting point of super austenitic stainless steel 1.4652 is as high as: 1320-1390°C; compressive strength (σb): ≥750MPa, tensile strength (σb): ≥430MPa, tensile strength: δ≥40%, strength: 250 (HB).

[0059] Super austenitic stainless steel 1.4652 has the following advantages:

[0060] Excellent corrosion resistance: 1.4652 stainless steel contains high levels of chromium and molybdenum, forming a stable passivation film, which makes it have excellent corrosion resistance. Whether in seawater, chemical media or high temperature environment, it can maintain good corrosion resistance.

[0061] Good mechanical properties: After solution treatment, 1.4652 stainless steel has high strength and toughness. This enables it to withstand large loads and impacts and meet the needs of various complex working conditions.

[0062] Good welding performance: 1.4652 stainless steel can be welded by common welding methods with good welding performance, which facilitates its application in various equipment and structures.

[0063] Easy to process and shape: 1.4652 stainless steel has good cold processing performance and can be processed and formed by forging, rolling and other processes. This makes it possible to manufacture components of various complex shapes.

[0064] Excellent high temperature performance: 1.4652 stainless steel can still maintain good mechanical properties and corrosion resistance in high temperature environment, and is suitable for equipment and structures under high temperature conditions.

[0065] Based on the above advantages and characteristics, the circular feeder made of 1.4652 super austenitic stainless steel in this example can meet the needs of long-term, high-temperature and high-speed stirring and vibration, and fundamentally solves the stability and life problems of long-term operation of processing equipment in high-temperature environments.

[0066] S5, continuously extruding the graphene-red copper mixed substrate so that the graphene as a filling element is completely extruded into the lattice gap of the red copper fine crystal structure to form a graphene composite copper strip blank;

[0067] Specifically, in this embodiment, a Conform continuous extruder is used to extrude the graphene-copper mixed substrate. At the same time, in order to ensure that the graphene retains a complete organizational structure when the copper substrate is melted, the extrusion die cavity temperature of the Conform continuous extruder in this embodiment is set to 800-950°C.

[0068] It should be noted that the composition of known copper scrap contains elements such as Cu, Ag, Au, Al, and Ni, and the lattice composition of the above elements is a face-centered cubic lattice, among which Zn and Ti are close-packed hexagonal lattices. The number of atoms in a single unit cell of the known face-centered cubic lattice and close-packed hexagonal lattice is 12.

[0069] The compactness of atomic stacking in a crystal is usually measured by "density". According to the density of atomic stacking, the face-centered cubic crystal plane and the close-packed hexagonal crystal plane are both atomic planes with the most compact arrangement of atoms of equal diameter. The atomic arrangement rules are exactly the same.

[0070] It is known that density refers to the ratio of the total volume occupied by atoms in a unit cell to the total volume of the unit cell, that is, the density formula is K=nv / V;

[0071] Where: K--crystal density;

[0072] N--The number of atoms actually contained in a unit cell:

[0073] V--the volume of an atom (rigid sphere), its value is 4πR 3 / 3 (R is the atomic radius);

[0074] V – total volume of unit cell.

[0075] From the above, we can know that the face-centered cubic density is: 0.74.

[0076] The density of hexagonal close-packed is: 0.74.

[0077] Among them, a and c are the edge lengths of the unit cell, also called lattice constants, and in hexagonal close-packed crystals c / a=1.633.

[0078] From this, we can see that the voids in the lattice of elements such as Cu, Ag, Au, Al, Ni, Zn, and Ti are 26%.

[0079] Since the element radius of graphene is small (the atomic diameter of C is 140pm under normal circumstances), which is much smaller than the atomic diameter of Cu (0.255nm), combined with the principle of copper alloy intermetallic compounds, normal valence compounds are composed of elements that are far apart on the periodic table and have a large difference in electronegativity. Metal elements and non-metals in groups IVA, VA, and VIA in the periodic table form compounds. The filler element graphene used in this implementation belongs to group IVA elements, so it can form compounds with metal elements in copper waste.

[0080] Based on the above factors, in order to ensure that graphene as a filling element can be completely squeezed into the 26% voids of the face-centered cubic lattice of Cu, Ag, Au, Al, and Ni, it is strengthened from within the element unit cell, and a dispersed filling and coating phase is formed around the original hard crystal core in the matrix, thereby forming a high-strength, high-conductivity filler.

[0081] This embodiment adopts a continuous extrusion process, and the extrusion pressure of the continuous extruder is set to not less than 1000Mpa. Thus, an extrusion force of not less than 1000MPa can be continuously generated. At this time, the solid-liquid ratio of the substrate is less than 40%, and the arrangement between the elements in the matrix is ​​disordered. Through extrusion and the subsequent cold rolling process, graphene forms a linear extension organization along the rolling and extrusion direction in the organization. These linear extension organizations constitute an efficient transmission channel for electrons, that is, effectively reducing the potential difference between the elements in the matrix, and effectively improving the conductivity and corrosion resistance of the composite material.

[0082] After the above process, we can obtain a graphene composite copper strip blank. The process in this embodiment can be used to prepare a graphene composite copper strip with a thickness of 16-25 mm and a width of 10-600 mm.

[0083] In order to prepare the finished graphene composite copper strip, the graphene composite copper strip blank is processed according to the conventional copper cold rolling process in this embodiment.

[0084] In this embodiment, graphene is fully squeezed into the lattice gap of copper waste as a filling element by combining a powder metallurgy process with a medium-temperature continuous extrusion process, forming a high-performance graphene composite copper strip with high strength, high thermal conductivity, high electrical conductivity, and high corrosion resistance. This preparation method not only realizes the efficient and pollution-free direct recycling of copper waste, but also realizes a substantial improvement in the physical and chemical properties of the composite material prepared from copper waste in terms of strength, electrical conductivity, corrosion resistance, high temperature resistance, and wear resistance.

[0085] Embodiment 2

[0086] It should be noted that the same process and the same components in the copper waste under the same process conditions have the same or similar performance effects on the graphene composite copper strip, which will not be repeated in this embodiment and the following embodiments.

[0087] Different from Example 1, in this embodiment, the copper scrap contains the following raw material components in mass percentage: Cu: 95-99.5%, Ag: 0.001-0.1%, P: 0.001-0.4%, Au: 0.0001-0.1%, graphene: 0.1-6%, and the remainder is one or more of Ni, Cr, Zn, Fe, Nb, Sn, Ti, Bi, Al, Pt, and B, and the total amount is less than 0.5%.

[0088] Based on the above-mentioned component content requirements, the copper waste materials selected in this embodiment are copper silver-plated waste materials, various graphics cards, memory sticks, and circuit board plug parts with gold plating.

[0089] It should be noted that the copper scrap in this embodiment contains 0.0001-0.1% Au. By utilizing the infinite solid solubility property of Au in Cu, the Au element filled with graphene is solid-dissolved in the copper matrix, which significantly enhances the critical shear stress of the alloy. At the same time, the enhanced matrix structure produced by graphene and Ag presents a refined crystal state, which greatly increases the wear resistance and high conductivity of the copper matrix.

[0090] Through the semi-melting crushing process, the grains are refined and the strengthening elements filled with graphene in the copper waste are evenly distributed in the copper matrix to form a highly conductive and high-strength strengthening phase.

[0091] The elastic modulus of the graphene composite copper strip prepared by the above-mentioned components in this embodiment can reach 131GPa, the yield strength is 275MPa, and the conductivity reaches 110%, which can be used for motor commutator commutator to meet the requirements of high conductivity, high strength and wear resistance. It greatly reduces the production cost, extends the service life of the commutator, and reduces the noise of high-power motor operation. Due to its high conductivity, it solves the problem of temperature rise of the commutator commutator and effectively avoids the occurrence of high-temperature fire problems caused by it. At the same time, it also solves the problem of power reduction caused by temperature rise.

[0092] Embodiment 3

[0093] Different from Example 1, in this embodiment, the copper scrap contains the following raw material components in mass percentage: Cu: 96-99.5%, Ni: 0.01-0.4, Sn: 0.01-0.1%, Ag: 0.001-0.1%, P: 0.01-0.1%, Au: 0.0001-0.1%, graphene: 0.1-4%, and the remainder is one or more of Cr, Zn, Fe, Nb, Ti, Bi, Al, Pt, and B, and the total amount is less than 0.5%.

[0094] Based on the above-mentioned component content requirements, the copper waste selected in this embodiment is waste recycled materials such as copper plated with Ag, Ni, Sn, etc.

[0095] The Ni and Sn in the organizational structure of this embodiment will produce a precipitated strengthening phase in the copper matrix. At the same time, the addition of graphene forms a filling structure between the strengthening phase and the copper grains, which reduces the potential difference of each element in the structure, greatly reduces the later galvanic cell reaction of the material, and enhances the corrosion resistance of the material matrix. The Au element is solid-dissolved in the copper matrix, which significantly enhances the critical shear stress of the alloy.

[0096] At the same time, the copper matrix grains present a fine-grained structure, which greatly improves the elasticity and strength indicators of the material. Through the linear extension of the graphene structure during the rolling and calendering process, an efficient electron transmission channel is formed, which greatly improves the conductivity of the matrix. Its conductivity value is increased by 20%, from the original 80% to 96%, reaching the conductivity of ordinary copper.

[0097] In addition, the composite material in this embodiment exhibits the characteristics of high elasticity and high strength. Specifically, the elastic modulus can reach 133 GPa, the yield strength is 280 MPa, and the electrical conductivity reaches more than 96%.

[0098] The composite material in this embodiment solves the problem of secondary use of waste materials after electroplating Ni and Sn.

[0099] At the same time, the composite material with high elasticity and high conductivity can completely replace the original high-conductivity and electroplating materials in electrical components, and this material will completely solve the material problem of electrical terminals. The fine-grained structure of the composite material in this embodiment can significantly extend the service life of the terminal and ensure the safety properties of the electrical terminal. It solves the problems of arcing, temperature rise and high-temperature corrosion when the terminal is on and off under load, improves the safety of electrical use, and eliminates the fire hazard caused by electrical appliances.

[0100] Embodiment 4

[0101] Different from Example 1, in this embodiment, the copper scrap contains the following raw material components in mass percentage: Cu: 97-99.5%, Fe: 0.01-0.5%, Ni: 0.01-0.5%, Ag: 0.001-0.01%, P: 0.01-0.1%, Au: 0.0001-0.1%, graphene: 0.01-5%, and one or more of other trace elements Cr, Zn, Nb, Ti, Bi, Al, Pt, and B, and the total amount is less than 0.5%.

[0102] Based on the above-mentioned component content requirements, the copper scraps selected in this embodiment are iron-containing copper such as KFC and C194, and copper scraps with nickel (Ni) and silver (Ag) plating on the surface.

[0103] In this example, Fe and Ni in the copper waste are used in the chemical reaction of Ag, combined with the semi-solidification stirring process, to homogenize the graphene structure that has been ball-milled and mixed. In the semi-solidification process, the good affinity between the iron hard crystal nucleus and graphene is used to fill the gaps of copper atoms growing around the iron crystal nucleus. Thus, the iron element is used as the crystal nucleus to limit the growth of copper grains, and then through the solid solution strengthening effect of Ni and copper elements, the anti-creep and softening temperature raising ability of Ag in the matrix are used, and a finer and strengthened organizational structure is obtained through the stirring and extrusion production process.

[0104] It should be noted that during the rolling and extrusion process, graphene forms a linear elongated structure, which constitutes an efficient electron transmission channel and can significantly improve the problem of Fe and Ni elements deteriorating conductivity.

[0105] The graphene composite copper strip prepared in this embodiment has the characteristics of high hardness, high temperature creep resistance, high conductivity, high strength, etc. Specifically, the conductivity reaches 103%, the elastic modulus can reach 129GPa, and the yield strength is 275MPa.

[0106] Embodiment 5

[0107] Different from Example 1, in this embodiment, the copper scrap contains the following raw material components in mass percentage: Cu: 98-99.5%, Ag: 0.001-0.5%, Au: 0.0001-0.1%, graphene: 0.1-8%, and the remainder is one or more of Ni, Cr, Zn, Fe, Nb, Sn, Ti, Bi, Al, Pt, B, and P, and the total amount is less than 0.5%.

[0108] Based on the above-mentioned component content requirements, the copper scrap selected in this embodiment is silver-plated copper scrap.

[0109] The graphene composite copper strip prepared in this embodiment has greatly improved the microhardness of the silver-copper alloy due to the support of the graphene linear organization. Specifically, graphene has excellent mechanical properties, and its unique two-dimensional structure and high-strength characteristics can effectively hinder the movement of dislocations inside the alloy when it is composited with the silver-copper alloy and presents a linear organizational distribution. The movement of dislocations when the material is subjected to external forces is an important microscopic mechanism that causes the deformation of the material. The graphene linear organization is like a "barrier" that makes it difficult for dislocations to move smoothly, thereby improving the ability of the silver-copper alloy to resist deformation, which is manifested macroscopically as an increase in microhardness.

[0110] At the same time, the enhanced matrix structure produced by the complementation of graphene and silver particles presents a fine-grained state, which greatly increases the wear resistance and high conductivity of the copper matrix. The test shows that the conductivity of the material is 115%, the elastic modulus can reach 120GPa, the yield strength is 255MPa, and the softening temperature is 350°.

[0111] The composite material prepared in this embodiment can replace the new Cu and Ag raw materials produced by furnace casting and the electrical moving contact and terminal materials after the electroplating process. Therefore, the energy consumption, various harmful emissions, environmental and water pollution and consumption in the electroplating process of the new material production link are greatly reduced, the material cost is reduced, and the production can be carried out by using social recycled waste materials. Its economic value is huge, and the material cost of the electrical industry will be greatly reduced.

[0112] Embodiment 6

[0113] Different from Example 1, in this embodiment, the copper scrap contains the following raw material components in mass percentage: Cu: 99.2-99.8%, Fe: 0.01-0.5%, Au: 0.0001-0.1%, graphene: 0.1-6%, and the remainder is one or more of Ag, Ni, Cr, Zn, Fe, Nb, Sn, Ti, Bi, Al, Pt, B, and P, and the total amount is less than 0.5%.

[0114] Based on the above-mentioned component content requirements, the copper scraps selected in this embodiment are KFC, C194 materials and some waste copper scraps with iron parts. Since the Au element in the alloy forms a face-centered cubic ordered solid solution with the Cu atom, the unit cell structure of Cu3Au and CuAu is a typical ordered arrangement when it is above 390°. Its ordered organizational structure can significantly enhance the critical shear stress of the alloy, increase the strength and hardness of the matrix, and improve the conductivity of the matrix. Through the Fe element in the copper scrap substrate, a hard crystal nucleus will be formed to prevent the crystallization and growth of the Cu element, and a fine-grained structure with Au and Fe elements as hard crystal nuclei will be obtained. In the above fine-grained structure, the graphene structure is pressed into the 26% lattice gap of the face-centered cubic structure through hot extrusion. The linear extension organization during the rolling and calendering process forms an efficient electron transmission channel, greatly improves the conductivity index of the matrix, and improves the plasticity of the substrate, thereby improving the bending property and fatigue resistance of the material, and realizing a high-strength, high-conductivity, and high-elongation copper alloy plate and strip

[0115] The graphene composite copper strip prepared in this embodiment has passed the test, and its conductivity reaches 96%, the elastic modulus can reach 131GPa, and the yield strength is 285MPa. This composite material can replace the C7025 nickel silicon material and tin phosphor bronze material used in high elastic components. It can achieve the huge effect of cost reduction, replacement and upgrading of materials when used in the lead frame substrate and high elastic relay terminal material industry.

[0116] The graphene composite copper strip prepared based on the above embodiments can be applied to conductive elastic components of aerospace, marine vehicles, automobiles, and conductive elastic components of electrical appliances.

[0117] The above is a specific implementation of the embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of this application.

Claims

1. A method for preparing graphene composite copper strip using copper waste, characterized in that: The steps include: S1, selecting copper waste containing different components according to the application scenario of graphene composite copper strip; S2, crushing the copper waste into copper block fragments; S3, according to the application scenario of the graphene composite copper strip, adding 0.1-8% by mass of graphene to the copper block scrap, and grinding to form a first size mixed powder; S4, semi-melting and stirring the first size mixed powder, so that the graphene is evenly filled in the copper fine crystal structure to form a graphene-copper mixed substrate; The S4 comprises the following steps: S41, feeding the first size mixed powder into a circular feeder, and injecting an inert gas into the circular feeder; S42, heating the circular feeder to 450-500° C. to make the first size mixed powder reach a semi-molten state to form the graphene-copper mixed substrate; S43, rotating and shearing the graphene-copper mixed substrate through the twin screws of the circular feeder, stirring for 10-20 minutes, and then conveying it to the discharge port of the circular feeder; S5, continuously extruding the graphene-red copper mixed substrate so that the graphene as a filling element is completely extruded into the lattice gap of the red copper fine crystal structure to form a graphene composite copper strip blank; S6, processing the graphene composite copper strip blank according to a conventional copper cold rolling process to obtain a graphene composite copper strip.

2. The method for preparing graphene composite copper strip using copper waste according to claim 1, characterized in that: The size of the copper block fragments is 1-2 cm, and the particle size of the first-size mixed powder is less than 50 μm.

3. The method for preparing graphene composite copper strip using copper waste according to claim 2, characterized in that: The circular feeder is made of super austenitic stainless steel 1.4652; the pushing pressure range of the twin screws is 35-45 MPa. At this time, the density of the graphene-copper mixed substrate is more than 65% of the normal solid theoretical density.

4. The method for preparing graphene composite copper strip using copper waste according to claim 1, characterized in that: The S5 comprises the following steps: S51, sending the graphene-copper mixed substrate into a continuous extruder; S52, setting the extrusion cavity temperature of the continuous extruder to 800-950° C., setting the extrusion pressure to not less than 1000 MPa, and continuously extruding the graphene-red copper mixed substrate to obtain the graphene composite copper strip blank.

5. The method for preparing graphene composite copper strip using copper waste according to claim 4, characterized in that: The continuous extruder is a Conform continuous extruder.

6. The method for preparing graphene composite copper strip using copper waste according to any one of claims 1 to 5, characterized in that: The graphene composite copper strip has a thickness of 16-25 mm and a width of 10-600 mm.

7. The method for preparing graphene composite copper strip using copper waste according to any one of claims 1 to 5, characterized in that: The graphene forms a linear extension structure for efficient electron transmission along the rolling and extrusion directions in the graphene composite copper plate and strip.

8. The method for preparing graphene composite copper strip using copper waste according to any one of claims 1 to 5, characterized in that: The copper scrap contains the following raw material components in percentage by mass: Cu: 95-99.5%, Ag: 0.001-0.1%, P: 0.001-0.4%, Au: 0.0001-0.1%, graphene: 0.1-6%, and the balance is one or more of Ni, Cr, Zn, Fe, Nb, Sn, Ti, Bi, Al, Pt, and B, and the total amount is less than 0.5%; Or, the copper scrap contains the following raw material components in percentage by mass: Cu: 96-99.5%, Ni: 0.01-0.4, Sn: 0.01-0.1%, Ag: 0.001-0.1%, P: 0.01-0.1%, Au: 0.0001-0.1%, graphene: 0.1-4%, and the balance is one or more of Cr, Zn, Fe, Nb, Ti, Bi, Al, Pt, and B, and the total amount is less than 0.5%; Or, in terms of mass percentage, the copper scrap contains the following raw material components: Cu: 97-99.5%, Fe: 0.01-0.5%, Ni: 0.01-0.5%, Ag: 0.001-0.01%, P: 0.01-0.1%, Au: 0.0001-0.1%, graphene: 0.01-5%, and one or more of other trace elements Cr, Zn, Nb, Ti, Bi, Al, Pt, and B, and the total amount is less than 0.5%; Or, the copper scrap contains the following raw material components in percentage by mass: Cu: 98-99.5%, Ag: 0.001-0.5%, Au: 0.0001-0.1%, graphene: 0.1-8%, and the balance is one or more of Ni, Cr, Zn, Fe, Nb, Sn, Ti, Bi, Al, Pt, B, and P, and the total amount is less than 0.5%; Or, measured by mass percentage, the copper scrap contains the following raw material components: Cu: 99.2-99.8%, Fe: 0.01-0.5%, Au: 0.0001-0.1%, graphene: 0.1-6%, and the remainder is one or more of Ag, Ni, Cr, Zn, Fe, Nb, Sn, Ti, Bi, Al, Pt, B, and P, and the total amount is less than 0.5%.

9. A graphene composite copper strip prepared by the method as described in any one of claims 1 to 8 is used for conductive elastic parts in aerospace, marine vehicles, automobiles and electrical appliances.

Citation Information

Patent Citations

  • Preparation method of copper matrix graphene alloy

    CN105063403A

Cited By

  • Graphene composite profile prepared from brass waste, preparation process and application

    CN119897469A

  • Graphene composite profiles prepared from brass waste, preparation process and applications

    CN119897469B